An analysis of 3D situation as a prospect for (LADM) in Nigeria: a Malaysian initiative - Babalola, Sunday Oyetayo (2015)
3D situation and development system of land administration is seen to be an immediate solution to land interest and land use complexity in our populated areas. The interest in land and the people relationship to the land in their Rights, Restrictions and Responsibilities (RRR) are the major challenges facing in the urban cities. 2D cadastre has proven to be incapable of handling some cities complexities and urban growth especially in the underground utilities, space above and below the surface of the earth. There is no visualization and modelling in our traditional 2D cadastre. 3D situation would help in the land administration because it is capable of storing, updating, analyzing, manipulating, quarrying and visualizing land RRR. The technical, legal and institutional aspect of 3D aspect provides a conceptual framework for the successful implementation and its development in Nigerian major cities. Therefore, this paper presents a case study approach to Malaysian 3D property situation because land administration in the two countries is similar. Malaysia has successfully developed and adopted 3D property development and implementation in most of their cities over the years. In view of this, we present the recent situation and current cadastral system as a prospect for Land Administration Domain Model (LADM) implementation in Nigeria. The successful implementation of 3D situation in Malaysia as an initiative for Nigerians was discussed. And finally, the solutions and advantages of 3D situation to the people and government of Nigeria were discussed.